Analisis Pengaruh Tingkat Profitabilitas, Kebijakan Dividen, Kekputusan Investasi dan Keputusan Pendanaan Terhadap Nilai Perusahaan Pada Perusahaan Jasa Sektor Perbankan yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2021 - Firda Amalia Rimananda; R. Gatot Heru Pranjoto (Jurnal Kajian Ilmu Manajemen (JKIM), 2022)
This study has an objective to determine the effect of profitability level, dividend policy, investment decision, funding decision either partially or simultaneously on company value in banking sector service companies listed on the Indonesia Stock Exchange for the 2016-2021 period. This study is conducted using quantitative method with the secondary data obtained from the Indonesia Stock Exchange. The population in this study are 47 banking companies listed on the Indonesia Stock Exchange for the 2016-2021 period. The sample in this study are 40 banking companies that have been determined using a purposive sampling technique. The data analysis technique used is multiple linear regression analysis. Based on the results of data analysis from the t statistical test or partially, the profitability variable (ROE) has a positive and significant effect on company value with a coefficient value of 5,074 and a significance level of 0.000 0.05, dividend policy (DPR) has a negative and insignificant effect on company value with a coefficient value of -1.229 and a significance level of 0.224 0.05, investment decision (FATA) has a positive and insignificant effect on company value with a coefficient value of 0.427 and a significance level of 0.671 0.05, and funding decision (DER) has a negative and insignificant effect on company value with a coefficient value of -1.641 and a significance level of 0.106 0.05. Meanwhile, the results of data analysis from the F statistical test show the Fcount value of 7.005 with the obtained probability value is smaller than alpha, which is 0.000 0.05. Thus, it can be concluded that the profitability level, dividend policy, investment decision and funding decision simultaneously have a positive and significant effect on company value. Moreover, the coefficient of determination (R2) obtained in this study is 0.267 or 26.70%.